The Role of Technique in Improving the Performance of Junior Swimmers - Bitang, Viorel; Liviu Andrei, Vasile; Viorel Petru, Ardelean; Dulceanu, Corina; Eleonora, ZÄƒgrean (Arena-Journal of Physical Activities, 2020)
Aim. Establishing a model of training as well as the judicious use of the most effective methods and means specific to and non-specific to swimming should lead to: - appropriate appropriation from the technical point of view of the 4 swimming procedures; - increasing the minimum driving qualities; - demonstrate the validity and applicability of methods used to follow the development of qualitative motor skills; Methods. In the general tendency to objectively human actions, there is also the need to rationalize the exercises used in training, hence the name â€žrationalization of effort on areas of intensityâ€. With these tests we tracked and scored with grades from 1 to 10 of the crawl technique and recorded the performance of athletes in the 50m free sample. The repetitions were performed on distances of 12.5m, 25m in a maximum of 8 repetitions. The usual statistical indicators were used: arithmetic average, amplitude, standard deviation and coefficient of variability. Results. Performance dynamics for 50m - arithmetic average, global, analyzing the entire period of research, reveals that the greatest leap in the results is between the second and the third tests (Init.T.= 40,47Â±4,38 sec and at the Fin. T. = 37,82Â±2,38 sec with a Dif. = 2,65 sec). Conclusions. Evaluation of technical performance. In addition to physical training under the training plan, special emphasis has been put on technical training, which at this age has a primordial role, knowing that incorrectly acquired skills, hardly or not at all, can be corrected later. The results obtained in the tests carried out have improved continuously, and finally the progress is obvious.